2019
DOI: 10.1088/1757-899x/526/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cold atmospheric pressure plasma jet against Enterococcus faecalis in apical canal of human single-rooted teeth: a preliminary study

Abstract: Many factors that may affect the success of root canal treatment are complexity of root canal system, especially in the apical part, and the virulence of bacteria such as biofilm formation. A cold atmospheric pressure plasma jet is a novel method for sterilization and applied for root canal disinfection. The purpose of this study was to investigate the effect of the cold atmospheric pressure plasma jet on Enterococcus faecalis (E. faecalis) biofilms infected in the apical root canals. Methods: Fifty-four singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[85,86] Furthermore, CAP has been found to have no negative effects on dental pulp stem cells, making it suitable for use in endodontic procedures. [82,83,[87][88][89][90] One study compared the effectiveness of traditional disinfectants with CAP using argon combined with 1% oxygen as a working gas on Candida albicans in human root canals. The study demonstrated that Plasma/O 2 treatment dramatically decreased the number of live C. albicans cells in extracted human teeth.…”
Section: Endodontic Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…[85,86] Furthermore, CAP has been found to have no negative effects on dental pulp stem cells, making it suitable for use in endodontic procedures. [82,83,[87][88][89][90] One study compared the effectiveness of traditional disinfectants with CAP using argon combined with 1% oxygen as a working gas on Candida albicans in human root canals. The study demonstrated that Plasma/O 2 treatment dramatically decreased the number of live C. albicans cells in extracted human teeth.…”
Section: Endodontic Diseasementioning
confidence: 99%
“…CAP jet and NaOCl were successful in removing E. faecalis biofilm, with the combination approach producing the most hopeful outcome. [90] Furthermore, a study that investigated the effects of NTAP treatment on human root dentin surfaces, on the recruitment, attachment, and growth of human dental pulp stem cells (hDPSCs), found that these surfaces supported improved hDPSCs attachment, spreading, subcellular activity, and proliferation, which may promote pulp-dentin regeneration in clinical settings. [87] When combined with traditional disinfectants, the use of CAP in endodontic treatment can have an additive effect on the removal of bacterial biofilms and the number of bacteria in infected root canals.…”
Section: Endodontic Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Its pathogenicity can be attributed to its high survival ability inside dentinal tubules [4,21,23]. Its environmental resistance is due to characteristics such as the species' capacity to form biofilms and ability to support high pH, such as the one used in intracanal medication with Ca (OH) 2 [24]. This pathogen tends to stand out when in a stable multi-species microbiota, becoming the dominant species [21].…”
Section: Infectious Endodontic Microbiotamentioning
confidence: 99%